Glucagon: Physiological and Pharmacological Functions and Pathophysiological Significance in Type 2 Diabetes - Tadahiro Kitamura (Endocrinology and Metabolism, 2024)
Glucagon has many functions, including the promotion of hepatic glucose production, fatty acid oxidation, thermogenesis, energy consumption, lipolysis, and myocardial contraction, as well as the suppression of lipogenesis, appetite, and gastrointestinal motility. However, it remains unclear which of these functions are physiological and which are pharmacological. Research on glucagon has lagged behind research on insulin because cross-reactivity with glucagon-related peptides in plasma has hindered the development of an accurate measurement system for glucagon. We recently developed a new glucagon sandwich enzyme-linked immunosorbent assay (ELISA) that is more specific and more sensitive to glucagon than the currently used measurement systems. The new sandwich ELISA is expected to contribute to personalized medicine for diabetes through its use in clinical examinations, the diagnosis of the pathophysiological condition of individual diabetes patients, and the choice of a treatment strategy. Efforts are continuing to develop glucagon/glucagon-like peptide-1 receptor dual agonists to improve obesity and fatty liver by enhancing glucagon’s appetite-suppressing and lipolysis- and thermogenesis-promoting effects. Thus, glucagon is expected to be applied to new diagnostic and therapeutic strategies based on a more accurate understanding of its functions.